Strengthening Student Assessment Skills Through School–Community Collaboration - Ainun Diana Lating; Sawal Mahaly; Jumail; Indah Hasni Pattimura (CV. TOTUS TUUS, 2025)
Assessment is a crucial step in planning and developing an effective guidance and counseling program. It plays a vital role in formulating appropriate goals, targets, and methods that align with the actual needs of the counselees. Without accurate assessment, a guidance and counseling program may lose direction and fail to meet its objectives effectively. The objective of this community service activity (PKM) is to assist guidance and counseling teachers in identifying students' problems and to develop students’ skills in using assessment tools. The implementation of the PKM activity was carried out through several stages, including preparation, implementation, mentoring, and evaluation. To achieve the goals of the PKM, several methods were applied, namely lectures and class discussions, group discussions, and question-and-answer sessions. The results of the PKM activity revealed that there are several issues among students that need to be addressed by guidance and counseling teachers. These include personal problems, which constitute the largest proportion at 42.6%, followed by learning-related issues at 34%, social issues at 12.7%, and career-related problems at 10.7%. The latter suggests that many students experience confusion or lack adequate information regarding their educational and career choices.